2001
DOI: 10.1054/bjoc.2001.1992
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of adipocyte G-protein expression in cancer cachexia by a lipid-mobilizing factor (LMF)

Abstract: Summary Adipocytes isolated from cachectic mice bearing the MAC 16 tumour showed over a 3-fold increase in lipolytic response to both low concentrations of isoprenaline and a tumour-derived lipid mobilizing factor (LMF). This was reflected by an enhanced stimulation of adenylate cyclase in plasma membrane fractions of adipocytes in the presence of both factors. There was no up-regulation of adenylate cyclase in response to forskolin, suggesting that the effect arose from a change in receptor number or G-protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 14 publications
(12 reference statements)
0
24
0
Order By: Relevance
“…Dexamethasone has been shown to stimulate adenylate cyclase catalytic activity and response to GTP in fat cell membranes (Lacasa et al, 1988). Zinc-a 2 -glycoprotein has also been shown to cause a three-fold increase in lipolytic response to isoprenaline, arising from changes in GTP-binding proteins (Gproteins), with an increased expression of Gas and a decreased expression of Gai in adipose tissue (Islam-Ali et al, 2001). ), EPA (50 mM) or SR59230A (10 mM) and the various inhibitors alone in a total volume of 2 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone has been shown to stimulate adenylate cyclase catalytic activity and response to GTP in fat cell membranes (Lacasa et al, 1988). Zinc-a 2 -glycoprotein has also been shown to cause a three-fold increase in lipolytic response to isoprenaline, arising from changes in GTP-binding proteins (Gproteins), with an increased expression of Gas and a decreased expression of Gai in adipose tissue (Islam-Ali et al, 2001). ), EPA (50 mM) or SR59230A (10 mM) and the various inhibitors alone in a total volume of 2 ml.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Elevated rates of lipolysis in cachexia would contribute to loss of total body fat only if lipid utilization were also increased. Indeed, clinical studies have reported elevated rates of whole body fatty acid oxidation in weight losing (10% of initial body weight) cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…32 Adipocytes from obese mice also express twofold lower levels of Gas, a stimulatory subunit of the guanosine triphosphate-binding protein, which stimulates adenylyl cyclase. 42 ZAG has been shown to increase the expression of Gas and decrease the expression of the inhibitory G-protein, Gai, in 3T3 adipocytes, 43 suggesting a mechanism by which ZAG could increase lipolytic responsiveness, in addition to the induction of HSL and ATGL. These results show that ZAG caused a major reduction in adipose mass in ob/ob mice.…”
mentioning
confidence: 99%